Iodine Deficiency and the Brain: Effects and Mechanisms. Issue 16 (9th December 2016) - Redman, Kahla; Ruffman, Ted; Fitzgerald, Penelope; Skeaff, Sheila
ABSTRACT: Iodine is an essential micronutrient needed in human diets. As iodine is an integral component of thyroid hormone, it mediates the effects of thyroid hormone on brain development. Iodine deficiency is the most prevalent and preventable cause of mental impairment in the world. The exact mechanism through which iodine influences the brain is unclear, but is generally thought to begin with genetic expression. Many brain structures and systems appear to be affected with iodine deficiency, including areas such as the hippocampus, microstructures such as myelin, and neurotransmitters. The clearest evidence comes from the studies examining cognition in the cases of iodine deprivation or interventions involving iodine supplementation. Nevertheless, there are many inconsistencies and gaps in the literature of iodine deficiency, especially over the lifespan. This paper summarizes the literature on this topic, suggests a causal mechanism for iodine's effect on the brain, and indicates areas for the future research (e.g., using magnetic resonance imaging (MRI) and functional MRI to examine how iodine supplementation facilitates cognitive functioning).